1998
DOI: 10.1515/bchm.1998.379.7.907
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication

Abstract: We have cloned two human putative steroid binding membrane proteins, termed Hpr6.6 and Dg6. Hpr6.6 is the human homolog of a previously cloned porcine progesterone binding protein. Both proteins contain a putative transmembrane domain and a highly conserved stretch of 58 amino acids. Hpr6.6 mRNA is expressed predominantly in liver and kidney, whereas Dg6 mRNA is preferentially expressed in placenta. Hpr6.6 is located on the X chromosome and dg6 on chromosome 4. The two proteins are the first putative steroid m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(22 citation statements)
references
References 80 publications
0
22
0
Order By: Relevance
“…In recent years, P4 is found to elicit a variety of fast, non-genomic effects on many physiological events, which are mediated by membrane P4 receptors, including PGRMC1 and PGRMC228 and mPRα, mPRβ as well mPRγ29. Missense mutations or reduced expression of PGRMC1 leads to premature ovarian failure (POF) in humans, which may be induced by the impaired binding of cytochrome P450 7A1 to PGRMC1213031.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, P4 is found to elicit a variety of fast, non-genomic effects on many physiological events, which are mediated by membrane P4 receptors, including PGRMC1 and PGRMC228 and mPRα, mPRβ as well mPRγ29. Missense mutations or reduced expression of PGRMC1 leads to premature ovarian failure (POF) in humans, which may be induced by the impaired binding of cytochrome P450 7A1 to PGRMC1213031.…”
Section: Discussionmentioning
confidence: 99%
“…We confirmed that PGRMC1 protein levels were increased in patients with PCOS compared with the controls (S3 Fig and S4 Fig). PGRMC1, approximately 22 kDa, was first described in 1998 [32] as a putative progesterone-binding membrane receptor [33]. Also, PGRMC1 is expressed in human ovarian granulosa and luteal cells [34, 35], and its expression level and subcellular localization is regulated by gonadotropins [36].…”
Section: Discussionmentioning
confidence: 99%
“…144 PGRMC1 also seems to play a role in the development of certain cancers, as recent reports suggest that it may be the inscrutable “sigma-2” receptor, a known biomarker of tumor cell proliferation. 145,146 In mammals, there exist two additional PGRMC1 family isoforms, PRGMC2/Dg6 147 and neudesin, 148 although it is not known if they also interact with CYP enzymes. PRGMC1 is highly expressed in the human liver and typically colocalized in the smooth endoplasmic reticulum (SER) with CYP proteins.…”
Section: Cytochrome P450 Interactions With Other Proteinsmentioning
confidence: 99%